Investigation of Thermal and Energy Performance of the Thermal Bridge Breaker for Reinforced Concrete Residential Buildings - Mi-Yeon Kim; Hyung-Geun Kim; Jin-Sung Kim; Goopyo Hong (Energies, 2022)
Thermal bridges in building envelopes can cause significant heat loss and heat gain. In this study, the developed thermal bridge breaker was applied to an interior insulation finishing system in residential buildings to minimize the thermal bridges in building envelopes. To investigate the thermal and energy performance of the developed thermal bridge breaker, the surface temperatures and heat flow at the wall and floor junctions were predicted using Physibel. In addition, the heating and cooling energy consumption in a residential building was analyzed by EnergyPlus. As a result, the use of the thermal bridge breaker can minimize the effective thermal transmittance in the building envelope system. Moreover, when the building envelopes were equipped with the thermal bridge breaker, the heating and cooling load through the exterior walls was decreased by 15–27%. Thus, the thermal bridge breaker can play an important role in minimizing the heat loss and occurrence of condensation in building envelopes.